Existence Of Right Ventricular Structural And Functional Changes In Essential Hypertension And Its Importance In Modern Medicine - Minashvili, Ana; Rekhviashvili, Ann (European Scientific Journal, ESJ, 2021)
The structural and functional changes of left and right ventricles as well as the existence of ventricular interaction in patients with arterial hypertenison (AH) were discussed in many research papers. Therefore, published data regarding right ventricular changes under influence of AH are scarce, non-univocal, and sometimes contradictory. Furthermore, there is a significant lack of clinical trials addressing the influence of circadian BP profile on RV structure and function. The importance of right ventricular function in maintaining global cardiac performance was proven. However, the importance of the right ventricular structure and function for cardiovascular morbidity and mortality is still under debate. Despite the abundance of the study data and high vulnerability of the right ventricle under influence of AH, the world's leading contemporary guidelines of the AH management, right ventricular remodeling, its morphology, function, evaluation, predictive and prognostic value are neither discussed nor mentioned. Hence, we strongly believe that further investigations are needed to determine the exact clinical utility and prognostic value of right ventricular functional and morphological changes in patients with arterial hypertension. Moreover, standardization and improvement of diagnostic methodologies of the RV changes via echocardiography, computed tomography, and Magnetic Resonance Imaging are important, which might have a crucial meaning for professionals involved in AH management. The review article aims to discuss anatomic and physiologic aspects of the right ventricle and their discrepancies according to age, sex, and race, the prognostic meaning of RV remodeling, and review current publications regarding the influence of high blood pressure and its circadian profile on the prevalence of functional and structural changes of RV. Hence, we performed a literature search of the PUBMED database using the medical subject headings "arterial hypertension", "essential hypertension", "systemic hypertension", "circadian BP profile", "remodeling", "right ventricle", "morphology", "anatomy" and "function". A manual search for additional studies was performed using references cited in the original articles.